Timer-based proteomic profiling of the ubiquitin-proteasome system reveals a substrate receptor of the GID ubiquitin ligase [Dataset] - Kong, Ka-Yiu Edwin; Fischer, Bernd; Meurer, Matthias; Kats, Ilia; Liu, Zhaoyang; Rühle, Frank; Barry, Joseph D.; Kirrmaier, Daniel; Chevyreva, Veronika; San Luis, Bryan-Joseph; Costanzo, Michael; Huber, Wolfgang; et al. (Universität, 2021)
Data accompanying the paper "Timer-based proteomic profiling of the ubiquitin-proteasome system reveals a substrate receptor of the GID ubiquitin l...
Gesehen am 10.03.2022
Keywords: Forschungsdaten; Datenbank